Sensitivity Enhancing of Oil Viscosity Sensor Based on Optical Fiber by Using Bending Angle Method - Yunus, Muhammad; Arifin, A; Fuadi, Nurul; Syafar, A. Muhammad (Politeknik Negeri Ujung Pandang, 2021)
Testing of oil viscosity sensor based on plastic optical fiber by using bending angle variation method to enhance the sensor sensitivity. This sensor is made by forming an optical fiber bending angle, it is dipped into the oil viscosity liquid. The light transmitted through into the optical fiber will be received by the photodetector and the measurement results are displayed on the OPM in the form of output power. The best measurement obtained at the bending angle of 300 with value of sensor sensitivity is 1.013 nW/mPa.s. This method has the advantage of high sensitivity in a simple measurement process.